Quantum Secure Direct Communication by Using Three-Dimensional Hyperentanglement - 施锦 龚彦晓 徐平 祝世宁 詹佑邦 (Communications in theoretical physics, 2011)
We propose two schemes for realizing quantum secure direct communication （QSDC） by using a set of ordered two-photon three-dimensional hyperentangled states entangled in two degrees of freedom （DOFs） as quantum information channels. In the first scheme, the photons from Bob to Alice are transmitted only once. After insuring the security of the quantum channels, Bob encodes the secret message on his photons. Then Alice performs single-photon two-DOF Bell bases measurements on her photons. This scheme has better security than former QSDC protocols. In the second scheme, Bob transmits photons to Alice twice. After insuring the security of the quantum channels, Bob encodes the secret message on his photons. Then Alice performs two-photon Bell bases measurements on each DOF. The scheme has more information capacity than former Q,SDC protocols.